Why do young people choose nursing as their future profession? – a qualitative study on polish nursing students’ motivating factors to apply to nursing and work in the profession after graduation - Artur Chmielewski; Piotr Przymuszała; Ryszard Marciniak (BMC Medical Education)
Abstract Background The existing staff shortages and growing worldwide demand call for action to increase the number of practicing nurses. Following the identified gap in the literature, this qualitative study aims to analyze what motivated nursing students to choose nursing as their field of study and whether they still plan to pursue it after graduation, including the factors influencing their intentions. Methods Thirty semi-structured interviews were conducted with nursing students from Poznan University of Medical Sciences (Poland) on this matter, and the obtained data were subjected to thematic analysis performed by two researchers. Before starting the study, its protocol was also submitted to the Poznan University of Medical Sciences Bioethics Committee, which decided that since it is not a clinical trial, its opinion is not necessary under the Polish legal system (Decision number: KB-987/22). Results Three themes were generated in this study. The first theme described what prompted respondents to apply for nursing studies. In this aspect, students mentioned factors like, e.g., their interests, subjects taken at high school, previous life experiences with the healthcare sector giving them a chance to observe nurses at work, having a nurse among family members or friends, or the positive presentation of healthcare professionals in the media or TV series. However, as the second theme demonstrated, some students reported a discouraging effect of negative reactions toward this choice from some family members, acquaintances, or even nurses, making them feel as if they had to defend this choice. The respondents attributed these reactions to some outdated stereotypical views on the nursing profession. Finally, the third theme summarized students’ current intentions to enter the profession after graduating and the factors influencing them, including the quality of their studies and whether they feel prepared for the requirements of the profession, the role of support and interpersonal relations among staff members, observed conditions of medical personnel’s work, physical and emotional burden and the responsibility of nurses’ work, the financial stability and abundance of different job prospects for nurses, or the issue of the prestige of the profession. Conclusions The study’s findings offer insight into the motives of nursing students for choosing nursing and their intentions to start working in the profession after graduation, which may help respond to identified problems, enhance the intentions of becoming a nurse among young people, and thus contribute to increasing the number of nurses in the healthcare sector.